2013
DOI: 10.1016/j.ihj.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of MDR1, CYP2C19 and P2Y12 genes in Indian population: Effects on clopidogrel response

Abstract: The present study did show a trend toward impaired response of clopidogrel to inhibit platelet aggregation with variant genotypes of CYP2C19*2 and iT744C of P2Y12 compared to respective wild type genotype at 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
4
37
2
3
Order By: Relevance
“…In Indian scenario, a study done in North Indian patients with CAD does not show any mutant genotypes for P2Y12 (i744T>C) polymorphism (Kar et al 2013). However, the study which was done on Maharashtrian, Gujarati, and Marwadi representing the western region of India showed a similar frequency distribution both in cases and controls as compared to that of the present study done in South Indian Tamilian population (Shalia et al 2013). This shows that there is significant intraethnic and interethnic variation in the distribution of variant alleles among Indians.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In Indian scenario, a study done in North Indian patients with CAD does not show any mutant genotypes for P2Y12 (i744T>C) polymorphism (Kar et al 2013). However, the study which was done on Maharashtrian, Gujarati, and Marwadi representing the western region of India showed a similar frequency distribution both in cases and controls as compared to that of the present study done in South Indian Tamilian population (Shalia et al 2013). This shows that there is significant intraethnic and interethnic variation in the distribution of variant alleles among Indians.…”
Section: Discussionsupporting
confidence: 75%
“…Henceforth, the exact role of P2Y12 polymorphism in association with CAD has to be substantially evaluated in clinical settings. Moreover, there are studies reporting the allele and genotype frequency of P2Y12 gene polymorphism in other populations (Azarpira et al 2011) (Shalia et al 2013) (Kar et al 2013), but to our knowledge, there is no data available for South Indian Tamilian population. Hence, the present study was aimed to determine the genotype and allele frequency of P2Y12 (i744T>C) gene polymorphism in the South Indian Tamilian population to predict its possible role in the development of CAD in this population.…”
Section: Introductionmentioning
confidence: 99%
“…CYP2C19*17 is associated with rapid metabolism of clopidogrel. 14 In Indian population the reported frequency CYP2C19*17 are in between 16% -35.5%. 7-10-14,15 Studies have shown that CYP2C19*17 variant is not independently associated with clopidogrel response and observed effect of this variant is due to LD with the CYP2C19*2 loss-of-function variant.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] In a study by Shalia et al, have observed that poor response to clopidogrel at 24 h with the variant genotypes of CYP2C19*2 as compared to wild type. 14 In one study, it has been reported that genetic contribution accounts for only approximately 12% of the response variability to clopidogrel. 18 However, it is unknown whether the time course of the antiplatelet effects of clopidogrel differs according to CYP2C19*2 phenotype in south Indian patients with ACS.…”
Section: Introductionmentioning
confidence: 99%
“…Several single nucleotide polymorphisms (SNPs) in the ABCB1 gene have been identified as candidates for CHD susceptibility; among them, C3435T (rs1045642 C > T) is the most common variant that has been widely investigated (Chowbay et al, 2005;Bournissen et al, 2009;Haerian et al, 2010). Recently, many studies have indicated that ABCB1 C3435T polymorphism might play a critical role in increasing CHD risk (Simon et al, 2009;Wallentin et al, 2010;Shalia et al, 2013). However, there is also some evidence that ABCB1 C3435T polymorphism had no effect on susceptibility to CHD (Poduri et al, 2009;Spiewak et al, 2009).…”
Section: Introductionmentioning
confidence: 99%